PELAKSANAAN KEGIATAN EKSTRAKURIKULER DI SEKOLAH DASAR NEGERI KOTA TANGERANG - Nurachman, Sunaryo (Perspektif Ilmu Pendidikan, 2020)
This study aims to evaluate the process of carrying out extracurricular activities in public elementary schools in the city of Tangerang. This study used a qualitative verification approach that was carried out in 8 schools. The results show that extracurricular activities at the school have been carried out very well especially for mandatory extracurricular activities. As for the non-mandatory extracurricular activities, the implementation varies greatly depending on the school’s policies and pupils’ interest which is supported by the presence of extracurricular choices. The coaching of extracurricular activities is carried out by the vice principal in the fields of curriculum, student affairs, teachers and alumni.